The New Century cyclopedia of names - Barnhart, Clarence Lewis, 1900-; Halsey, William Darrach, 1918- (Prentice-Hall, 1977)
This is a unique reference work consisting solely of information about proper names having importance in the English-speaking world. English and native spellings, pronunciations, and essential facts are given about more than 100,000 names such as persons, places, events, plays and operas, works of fiction, literary characters, works of art, mythological and legendary persons and places, etc.